Use of wide bore bougie (36Fr) and small distance of staple line from Pylorus (≤4cm) as predictor of success of Laparoscopic Sleeve Gastrectomy - Junaid Khan Lodhi, Aasim Malik, Saba Tahir Bukhari, Saima Amjad, Rutb Shereen, Muhammad Zubair (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Laparoscopic sleeve gastrectomy is now a gold standard treatment for morbid obesity but no local data is available to standardize size of bougie and distance of staple line from pylorus and its effect on weight loss. Aim: To evaluate effect of 36 Fr bougie size and a distance of staple line of ≤4cm from pylorus and its impact on outcome of LSG. Method: This is retrospective study done by going through data base of morbidly obese patients from Jan 2012 to Dec 2020. Results: 150 patients were included in the study. Mean age of patients was 42 years old and male to female ratio was 4:11. Preoperative BMI was 56 kg/m². Operative time was 102 ±13.24 minutes. Postoperative leak was seen in 2 (1.6%) cases with total 7 patients developing complication with 1(0.6%) mortality. Mean follow up was 34.21±13.68 months. Percentage of weight loss observed was 30%,50%,55%,58%,60% and 60% at 6 months,1 year and then yearly after till 5 years. At 5 years, DM, HTN, OSAS, DJD and HLP showed remission of 75%,90%, 58%, 40% and 82% cases respectively. No revisional surgery was performed. Conclusion: LSG is a definitive bariatric procedure not only safe in expert hands but also effective and durable %WL is mainly dependant on bougies of 36 Fr size and a distance of ≤ 4cm of staple line from pylorus.